LATE MIOCENE CLIMATE IN THE CIRCUM-ALPINE REALM-A QUANTITATIVE ANALYSIS OF TERRESTRIAL PALAEOFLORAS - Bruch A.A.; Mosbrugger V.; Utescher T.; Gabrielyan I.; Ivanov D.A. (My University, 2006)
Selected mega- and microfloras from Central and Southern Europe have been analysed for the time interval Tortonian/Pannonian (MN 9-12) with the Coexistence Approach to obtain quantitative palaeoclimate data. The results give a geographically differentiated picture of the Late Miocene climate in the circum-Alpine area. Spatial patterns are presented in maps for mean annual temperature, temperature of the coldest month, temperature of the warmest month, mean annual precipitation, and mean annual range of temperature. The obtained data show an overall warm, humid, and homogenous climate with very low latitudinal and longitudinal gradients; there is no indication of a Mediterranean type of climate. Palaeogeographic influences on climate patterns are evident; the Pannonian Lake caused mild winters and a lower seasonality of temperature in the Pannonian basin. © 2006 Elsevier B.V. All rights reserved.
Keywords: CENTRAL EUROPE; PALAEOCLIMATE MAPS; QUANTITATIVE ANALYSIS; TERRESTRIAL ENVIRONMENT; UPPER MIOCENE; Tortonian; Cenozoic::Neogene::Miocene::Tortonian; Кайнозой::Неоген::Миоцен::Тортонский